STUDY ANTIBACTERIAL ACTIVITY OF LAURUS NOBILIS LEAVES WATER EXTRACT ON SOME ISOLATES OF PATHOGENIC BACTERIA - B. H. Saleh,; H.N. Yahya,; R N. Ibrahim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to isolation of pathogenic bacteria from different clinical cases like burns, wounds &UTI infections, then study the antimicrobial activity of Laurus nobilis leaves water extract on it. From a total of (80) samples were taken from these cases, the most isolated bacteria were related to Pseudomonas aeruginosa, Klebsiella pneumoniae, Staph aureus & Escherichia coli. Antibiotic sensitivity test was done for isolated bacteria against (9) antibiotic and most of them revealed sensitivity to gentamycin, ciprofloxacin& trimethoprim/ sulphamethoxazole. Different concentration of Laurus nobilis leaves water extract (25, 50, 100, 200) mg/ml were tested for detection its antibacterial activity against isolated bacteria .Results revealed that concentration (50, 100, 200) mg/ml revealed high antibacterial activity against Staph aureus & Klebsiella pneumoniae, also showed intermediate level against Escherichia coli, while higher concentration only (100, 200) mg/ml of extract revealed antibacterial activity against Pseudomonas aeruginosa